Dependence of annealing time on structural and morphological properties of Ca(Zr0.05Ti0.95)O-3 thin films - Cavalcante, L. S.; Simões, Alexandre Zirpoli [UNESP]; Orlandi, Marcelo Ornaghi [UNESP]; Santos, M. R. M. C.; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Elsevier B.V. Sa, 2008)
Ca(Zr0.05Ti0.95)O-3 (CZT) thin films were prepared by the polymeric precursor method by spin-coating process. The films were deposited on Pt(1 1 1)/Ti/SiO2/Si(1 0 0) substrates and annealed at 650 degrees C for 2,4, and 6 It in oxygen atmosphere. Structure and morphology of the CZT thin films were characterized by the X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FT-IR), atomic force microscopy (AFM) and field-emission scanning electron microscopy (FEG-SEM). XRD revealed that the film is free of secondary phases and crystallizes in the orthorhombic structure. The annealing time influences the grain size, lattices parameter and in the film thickness. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: atomic force microscopy; crystallization; diffusion; growth mechanism